The Effect of Control System Maturity and the Government Internal Oversight Capability Level on Audit Opinions - Prakoso, Faisal; Aryati, Titik (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
This research aims to evaluate the impact of the maturity of the Government Internal Control System (Sistem Pengendalian Intern Pemerintah/SPIP), the level of capability of the Internal Government Supervisory Apparatus (Aparat Pengawasan Intern Pemerintah/APIP), and Performance Accountability measured by the Government Performance Accountability System Index (Sistem Akuntabilitas Kinerja Instansi Pemerintah/SAKIP) on the audit opinion of Local Government Financial Statements (Laporan Keuangan Pemerintah Daerah/LKPD). The data used in this research are the results of BPKP's evaluation for SPIP maturity, the level of APIP capability assessed through quality assurance by BPKP, SAKIP index assessed by the Ministry of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia, and audit opinions on LKPD issued by BPK RI for the years 2018, 2019, 2020, 2021, and 2022 for Local Governments. From a population of 542 local governments, this research sampled 520 Local Governments over 5 years (2018 to 2022) using secondary data, with a total of 2600 processed data. The results of the research indicate that the maturity level of SPIP, the capability level of APIP, and performance accountability have a positive impact on the issuance of audit opinions on LKPD. Therefore, improving SPIP maturity, APIP capability, and enhancing performance accountability can increase the accountability, reliability, and fairness of local government financial statements in obtaining Unqualified Opinion (Wajar Tanpa Pengecualian/WTP).